Pengembangan bahan ajar interaktif dengan pendekatan saintifik bermuatan nilai-nilai karakter pada materi hukum newton tentang gerak dan hukum newton tentang gravitasi di kelas X SMA/MA - Mutia Risma; Murtiani Murtiani; Yenni Darvina; Yulkifli Yulkifli (Universitas Negeri Padang, 2019)
This research intends to produce interactive teaching materials that has been valid and practical tested. The use of interactive teaching materials that can support the learning process of Physics is one of the most appropriate solutions, namely learning material is presented in the steps of the scientific approach and contains character values. This research is a research and development (R&D) type that uses Sugiyono development model. Sugiyono development model has ten phases, that is potential and problems phases, data collection phase, product design phase, design validation phase, design revisions phase, product trials phase, product revision phase and mass production phase. But this research uses five phases only, that is potential and problems, data collection, product design, design validation, and design revisions phase. For validity and practicality test this research uses questionnaire instruments. The validy questionnaire instrument is filled by three Physics major of FMIPA UNP’s lecturers as the validators. For practicality questionnaire instrument is filled by three teachers and twenty five students of SMA Pembangunan Laboratorium UNP as the practitioners. Finale data of the questionnaire instrument is analyse by using Likert scale. From validity test, the developed interactive teaching material is rated very valid with percentage average score 83,8 %. From practicality tests, the developed interactive teaching material is rated very practice by teachers and students with percentage average score by teachers 88,3 % and percentage average score by students 88,3 % too. It means that the developed interactive teaching material is proper to be used in school as learning media.